2015
DOI: 10.1039/c5ce01213a
|View full text |Cite
|
Sign up to set email alerts
|

Bis(paracetamol) pyridine – a new elusive paracetamol solvate: from modeling the phase diagram to successful single-crystal growth and structure–property relations

Abstract: Multi-component crystals -salts, co-crystals, or solvates -are usually designed based on the analysis of complementarity of functional groups and intermolecular interactions of the components. However, no crystal design can do without a practical method of crystal growth. Not all compounds that should be 10 expected to exist based on the "synthon approach" can be prepared in real experiments. This paper aims to illustrate that, in addition to the synthon approach, it is equally important to take into account p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…High pressure can influence the course of crystallization of materials and the weak hydrogen bonds are relevant for the formation of new polymorphs or solvates. For all dabco salts studied at high-pressure conditions, either new phases or solvates were formed. Likewise, we have found that dabcoHBF 4 forms a hydrate at 1.06 GPa, when crystallized from water solution. No other solvates have been obtained, although recrystallizations of dabcoHBF 4 from methanol or ethanol or their 1:1 or 3:1 mixtures with water in isochoric conditions were tried.…”
Section: Results and Discussionmentioning
confidence: 71%
“…High pressure can influence the course of crystallization of materials and the weak hydrogen bonds are relevant for the formation of new polymorphs or solvates. For all dabco salts studied at high-pressure conditions, either new phases or solvates were formed. Likewise, we have found that dabcoHBF 4 forms a hydrate at 1.06 GPa, when crystallized from water solution. No other solvates have been obtained, although recrystallizations of dabcoHBF 4 from methanol or ethanol or their 1:1 or 3:1 mixtures with water in isochoric conditions were tried.…”
Section: Results and Discussionmentioning
confidence: 71%
“…† Solvates of paracetamol have been reported in 1,4-dixoane 88 and pyridine. 89 Therefore, these solvents were excluded from the solvent screen as the target polymorph was the monoclinic form I.…”
Section: Stage 1: Prior Knowledgementioning
confidence: 99%
“…In both co-crystals, the 1D hydrogenbonded chains stack to form layered structures. Additional cases of synthon diversity with PCA have been demonstrated in other co-crystals and numerous hydrate and solvate structures [51][52][53][54][55][56].…”
Section: Pharmaceuticals With Multiple Hydrogen-bond-donor Sites: Co-crystals Involving Paracetamol and Polyphenolsmentioning
confidence: 99%